2016
DOI: 10.3389/fendo.2016.00137
|View full text |Cite
|
Sign up to set email alerts
|

Paraventricular Hypothalamic Mechanisms of Chronic Stress Adaptation

Abstract: The hypothalamic paraventricular nucleus (PVN) is the primary driver of hypothalamo–pituitary–adrenocortical (HPA) responses. At least part of the role of the PVN is managing the demands of chronic stress exposure. With repeated exposure to stress, hypophysiotrophic corticotropin-releasing hormone (CRH) neurons of the PVN display a remarkable cellular, synaptic, and connectional plasticity that serves to maximize the ability of the HPA axis to maintain response vigor and flexibility. At the cellular level, chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
160
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(178 citation statements)
references
References 112 publications
(134 reference statements)
7
160
1
10
Order By: Relevance
“… How these changes in AD may influence HPA axis activation is less clear. In animal studies, LC projections to the PVN are present, although the substantial proportion noradrenergic input comes from the nucleus of the solitary tract . There also may not be detectable differences in NE measured in the hypothalami of AD subjects compared with controls .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“… How these changes in AD may influence HPA axis activation is less clear. In animal studies, LC projections to the PVN are present, although the substantial proportion noradrenergic input comes from the nucleus of the solitary tract . There also may not be detectable differences in NE measured in the hypothalami of AD subjects compared with controls .…”
Section: Discussionsupporting
confidence: 87%
“…These range from direct projections and indirect paths between brain structures, signaling through peripheral sympathetic input, and glucocorticoid negative feedback. 2,22 Given the complexity of the relationships between these 2 stress systems, it is not surprising that we did not find the association between CSF cortisol and CSF NE in controls we had anticipated. These multiple regulatory mechanisms likely obscure finding a significant relationship between CSF NE and CSF cortisol, particularly as the latter hormone is derived from the periphery and must cross the blood brain barrier.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Studies also suggest a complex role for the CRF system in social behaviour. Indeed, AVP is co-released with CRF from the paraventricular nucleus of the hypothalamus (PVN) to potentiate stress responses, whereas OT reduces the stress-induced PVN-CRF transcription (Bulbul et al, 2011;Jurek et al, 2015;Herman and Tasker, 2016). administration of CRF facilitates partner preference in male prairie voles (DeVries et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated stress‐induced changes in the GABAergic regulation of CRH neurons, including altered GABA A R subunit expression, a reduction in presynaptic GABA release, and overall impairments in GABAergic signalling onto CRH neurons (Herman & Tasker, ). The CORT‐mediated effects on the GABAergic regulation of CRH neurons demonstrated in Colmers & Bains () may contribute to these stress‐induced changes in GABAergic regulation of CRH neurons.…”
mentioning
confidence: 99%